Development of an Interactive Program to Study of the Continuation Power Flow - Canossa, J. H.; Bonini Neto, A. [UNESP]; Alves, D. A. [UNESP]; Putti, F. F. [UNESP]; Gabriel Filho, L. R. A. [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2018)
In this paper an interactive program developed to study of the continuation power flow is presented. Both, the graphical user interface and the power flow program have been developed in the Matlab environment thus providing a good computational performance and a users-friendly teaching software. The interactive program allows the user to edit the input and output data files of the selected power systems as well as to visualize and analyze the results directly on the computer screen. Directly from the system one-line diagram, the graphical interface allows the user change the parameters of the system (bus and lines system data); remove the transmission line clicking directly on it; view the buses voltage and angle profiles and the real and reactive power flows. In order to assess the current operating point condition, the user can also obtain the pre- and post-contingency loading margins by tracing the respective P-V curves. All these characteristics make the developed program recommended for educational purpose.
Keywords: Power engineering education; P-V curve; Continuation power flow; Power flow analysis